Effect of rice husk blending on combustion characteristics of high ash Indian coal analyzed in TGA. Issue 12 (2nd December 2022) - Kumar, Pritam; Nandi, Barun Kumar
ABSTRACT: Present work reports the effects of rice husk (RH) blending on combustion characteristics of high ash Indian coal. Combustion experiments were carried out using the thermogravimetric analyzer (TGA). Combustion performance of coal, RH, and coal-RH blends were assessed through identification of ignition temperature (TI ), peak temperature (TP ), burnout temperature (TC ) along with ignition index (IIX ), combustion characteristics index (CIX ), burnout index (BIX ), heat intensity index (HIX ), activation energy (AE), and thermodynamic parameters ( Δ H, ΔG, and ΔS) analysis. Experimental results show that with the increase in RH mass in coal up to 50%, TI decreased from 418 to 263°C, TP decreased from 468 to 450°C, TC decreased from 499 to 490°C, and AE reduced from 84.84 to 72.42 kJ/mol, inferring substantial enhancement in coal combustion performance. Δ H, ΔG, and ΔS analysis showed that with 50% RH in coal reduced from 78.66 to 67.11 kJ/mol, ΔG improved from 147.62 to 57.66 kJ/mol, ΔS varied from −92.48 to 15.99 J/mol.K, concluding blending of RH eases the combustion.